Pharmacoeconomical Consequences of Postoperative CSF Leaks After Intracranial Surgery – A Prospective Analysis - Piek, J.; Weber, C.; Kundt, G.; Tronnier, V.; Spuck, S.; Hirdes, C.; Kehler, U.; Ditges, C. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Cerebrospinal fluid (CSF) leaks are well-known and frequent complications of intracranial procedures with their clinical aspects covered by numerous studies. Little, however, is known about the pharmacoeconomical aspects of this specific complication. 545 patients with a variety of intracranial procedures (elective and trauma) were recruited for a multicenter, prospective, observational study over a 13-month period. A specific pharmacoeconomic analysis was performed in 168 of these patients from the institution of the first author covering all clinical and pharmaco-economical aspects of this specific complication. Of all patients, 5.36% developed a postoperative CSF leak. Treatment of the leak required numerous diagnostic and therapeutic procedures such as reoperations (n = 6), lumbar punctures (n = 11) or lumbar drainages (n = 4). Costs for these procedures and prolonged hospital stays nearly doubled the costs per case (€14079/case without a fistula vs. €25499/case with a fistula). Reimbursement for the hospital covered these extra costs, but net earnings per case were diminished by €565 in cases with a CSF leak. The authors conclude that the presence of a CSF leak after an intracranial operation – although not influencing outcome in general – results in additional diagnostic and therapeutic procedures for the patient, an enormous increase in costs for the community, and a financial loss for the hospital. Strategies to lower this complication rate should therefore urgently be developed both from a clinical and a pharmacoeconomical point of view.
Keywords: cranial surgery; brain tumor; head injury; CSF fistula; DRG system